2023
DOI: 10.1108/tr-07-2022-0340
|View full text |Cite
|
Sign up to set email alerts
|

Visiting natural disaster sites as transformational experiences

Abstract: Purpose This study aims to investigate the perceived benefits arising from tourist activities at natural disaster sites, to analyze the influence of perceived benefits on satisfaction and behavioral intentions and to identify origin region’s moderating role. Design/methodology/approach A research model containing dark tourism motivations (DTMs), tourist perceived benefits (TPBs), tourist satisfaction (TS), protection intention (PI) and loyalty intention (LIs) was developed, and visitor origin was introduced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 91 publications
(156 reference statements)
0
5
0
Order By: Relevance
“…Tourists understood the emotions of others and appreciated the lessons learned. Aligned with Hwang et al (2022) and Wang et al (2023), this research also revealed that the tourists embodied and transformed their emotions through their visiting experiences in the dark tourism sites.…”
Section: Discussion On the Emotional Experience Of Disaster Tourismmentioning
confidence: 75%
See 2 more Smart Citations
“…Tourists understood the emotions of others and appreciated the lessons learned. Aligned with Hwang et al (2022) and Wang et al (2023), this research also revealed that the tourists embodied and transformed their emotions through their visiting experiences in the dark tourism sites.…”
Section: Discussion On the Emotional Experience Of Disaster Tourismmentioning
confidence: 75%
“…Lewis et al (2022) considered that personal beliefs matter more than outside influence from others. Wang et al (2023) empirically found that tourist's perspectives and attitudes towards ruins sites, which the results showed that disaster memorials' perception positively influences the positive evaluation of dark tourism. Fabros et al (2023) identified seven tourist motivations for visiting dark tourism sites that have emerged in the study: education, remembrance, sightseeing, recreation, family bonding, curiosity, and event venue.…”
Section: Tourist Motivationmentioning
confidence: 93%
See 1 more Smart Citation
“…2.3.1 Dynamic capability in the context of tourism. Dynamic capability theory has been widely applied in the field of tourism, with research covering three main areas: managing crises and disasters, influencing factors of dynamic capability and the relationship between dynamic capability and enterprise (tourism destination) performance, competitiveness and knowledge innovation (Wang et al, 2023). Facing the impact of COVID-19 on the tourism industry, dynamic capability enables tourism organizations to respond to disruptive environmental changes through conventional transformation, resource allocation and utilization processes (Jiang et al, 2021a).…”
Section: Dynamic Capabilitymentioning
confidence: 99%
“…This study examined the awe inspired by nature, but other stimuli such as historical, cultural, or religious resources and environments can also trigger awe (Keltner and Haidt, 2003). In particular, Wang et al (2023) considered visiting dark tourism destinations a transformational experience. It implies the possibility of evoking awe through "dark elicitors" (e.g.…”
Section: Limitations and Future Researchmentioning
confidence: 99%